As Brave As You - Reynolds, Jason (New York : Atheneum Books for Young Readers, 2016)
When Genie and his older brother spend their summer in the country with their grandparents, he learns a secret about his grandfather and what it means to be brave.
Keywords: Grandparent and child -- Juvenile fiction; Brothers -- Juvenile fiction; Courage -- Juvenile fiction; Blind -- Juvenile fiction; Country life -- Juvenile fiction; African Americans -- Juvenile fiction; Grandparent and child -- Fiction; Brothers -- Fiction; Courage -- Fiction; Blind -- Fiction; Country life -- Fiction; African Americans -- Fiction